Response of high yielding varieties of sugarcane (Saccharum officinarum) to waterlogging - Gandia, Jayson L.; Delfin, Evelyn F.; Descalsota, Michelle Lyka V.; Samson, Emmanuel G.; Peña, Mark C. (2021)
"Unfavorable weather in the Philippines leaves the sugarcane industry vulnerable to losses from flooded fields. A system of identification should be developed to supplement the country's lack of sugarcane varieties tolerant to waterlogging. This study investigated the effect of waterlogging imposed during the early stalk elongation stage on sugarcane grown in contrasting soil types. In 2017-2018, two split-plot trials at the Institute of Plant Biology (IPB) University of the Philippines (UP) Los Baños experimental area and UP La Granja (La Carlota City, Negros Occidental) evaluated the response of 10 high yielding varieties (HYVs) to flooding for 2wk during stalk elongation stage [6 mo after planting (MAP)]" - title page.
Includes bibliographical references.
Keywords: Sugar crops -- Philippines -- Negros Occidental; Sugar plantations -- Philippines -- Negros Occidental; Waterlogging (Soils) -- Philippines -- Negros Occidental